The meaning of the word something in the Koranic context" Elbakara and Al-Imran sample - جادر حسن كزار (lark, 2019)
This research intends to one of the words of our precious language to highlight it, the word (something), has expanded its significance to denote everything, as it revolves and takes place in tongues, has the freedom and will in the lexicon of each speaker without considering the amount of knowledge, so this research is busy access To the origin of its meaning in the Arabic miracles, and to see their significance in the Koran, through tracking the Quranic employment using the contextual significance of the sacred text, the research came in three demands, the first looks at the contextual significance and trends, and the second looking for the meaning of the word in its lexical significance, and the third monitors the semantics That campaigned The term in the Koran, and clear from our research that the word (something) in the lexicon common name of the meaning of an existing zero, meaning in the Abyssinian language of destruction and genocide, the Koran has ridiculed the word thing for many indications of more than thirteen significance in Surat al-Baqarah and Imran.